Section zero: there is no section zero ebook There is no section zero. - Kesel, Karl (Section Zero (2019)., 2019)
A team of fearless adventurers band together to protect humankind from everything that doesn't exist. If JACK KIRBY had created The X-Files, it would look a lot like SECTION ZERO! This graphic novel from one of comics classic creative teams KARL KESEL (Harley Quinn, Superboy) and TOM GRUMMETT (Death of Superman, Superboy) includes pin-ups by some of the greatest artists in comics, including GEORGE PEREZ (Avengers), DAVE GIBBONS (Watchmen), WALTER SIMONSON (Thor), and many more! Collects SECTION ZERO #1-6, plus extras!. Author: Karl Kesel. Illustrator: Karl Kesel, Tom Grummett . 2019 KARL KESEL & TOM GRUMMETT.